Main morbidities recorded in the women's international study of long duration oestrogen after menopause (WISDOM): a randomised controlled trial of hormone replacement therapy in postmenopausal women. Issue 7613 (11th July 2007) - Vickers, Madge R; MacLennan, Alastair H; Lawton, Beverley; Ford, Deborah; Martin, Jeannett; Meredith, Sarah K; DeStavola, Bianca L; Rose, Sally; Dowell, Anthony; Wilkes, Helen C; Darbyshire, Janet H; Meade, Tom W
Abstract : Objective To assess the long term risks and benefits of hormone replacement therapy (combined hormone therapy versus placebo, and oestrogen alone versus combined hormone therapy). Design Multicentre, randomised, placebo controlled, double blind trial. Setting General practices in UK (384), Australia (91), and New Zealand (24). Participants Postmenopausal women aged 50-69 years at randomisation. At early closure of the trial, 56 583 had been screened, 8980 entered run-in, and 5692 (26% of target of 22 300) started treatment. Interventions Oestrogen only therapy (conjugated equine oestrogens 0.625 mg orally daily) or combined hormone therapy (conjugated equine oestrogens plus medroxyprogesterone acetate 2.5/5.0 mg orally daily). Ten years of treatment planned. Main outcome measures Primary outcomes: major cardiovascular disease, osteoporotic fractures, and breast cancer. Secondary outcomes: other cancers, death from all causes, venous thromboembolism, cerebrovascular disease, dementia, and quality of life. Results The trial was prematurely closed during recruitment, after a median follow-up of 11.9 months (interquartile range 7.1-19.6, total 6498 women years) in those enrolled, after the publication of early results from the women's health initiative study. The mean age of randomised women was 62.8 (SD 4.8) years. When combined hormone therapy (n=2196) was compared with placebo (n=2189), there was a significant increase in the number of major cardiovascular events (7 v 0, P=0.016) and venous thromboembolisms (22 v 3, hazard ratio 7.36 (95% CI 2.20 to 24.60)). There were no statistically significant differences in numbers of breast or other cancers (22 v 25, hazard ratio 0.88 (0.49 to 1.56)), cerebrovascular events (14 v 19, 0.73 (0.37 to 1.46)), fractures (40 v 58, 0.69 (0.46 to 1.03)), and overall deaths (8 v 5, 1.60 (0.52 to 4.89)). Comparison of combined hormone therapy (n=815) versus oestrogen therapy (n=826) outcomes revealed no significant differences. Conclusions Hormone replacement therapy increases cardiovascular and thromboembolic risk when started many years after the menopause. The results are consistent with the findings of the women's health initiative study and secondary prevention studies. Research is needed to assess the long term risks and benefits of starting hormone replacement therapy near the menopause, when the effect may be different. Trial registration Current Controlled Trials ISRCTN 63718836